Estimation of Tsunami Inundation and Disaster Mitigation in Bulukumba, Indonesia - Imanuela I. Pertiwi; Muhammad H. Fattah; Abdul Rauf (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
The study aims to determine the potential of earthquake that could lead to tsunamis in the Flores Sea. Furthermore, based on the potential of earthquake magnitude, can be known high run-up of tsunami in the southern coastal region of Bulukumba regency. The height run-up of tsunami can show the vulnerability of tsunami impact and eects spatially based on the eect of land function in the southern coastal area of Bulukumba Regency. To plan an eective mitigation scenario in the southern coastal area of Bulukumba Regency can be based on the vulnerability of tsunami impacts and eects. This study uses secondary data consisting of three data. The condition of land function and the density of community infrastructure is obtained basedon RTRW data of Bulukumba District and Satellite Bing Maps image data; historical data of earthquake events inthe Flores Sea from 1927 to 2016 from the USGS site, and BMKG; as well as topographic data. Field check activityon land function condition is done as a form of conformity of secondary data. The results showed that the potential of seismicity in the Flores Sea is high, with magnitude (M 7 SR) potentially causing tsunamis around it, not least Bulukumba Regency, South Sulawesi Province, Indonesia. The area of tsunami inundation in Bulukumba Regency is 13.617 km2. The coastal area of Ujungbulu sub-district is a dense residential area that has the highest risk to the tsunami with an estimated 3,331 km2 inundation. Land cover in Bontotiro sub-district dominated by vegetation with kerapatandengan interval distance of more than 3 m is seen able to reduce the tsunami with a height of 17 m and 25 m. Tsunami disaster mitigation scenario in Bulukumba regency is to make coastal area as conservation area of coastal forest (mangrove plant) that function as green belt of tsunamiwave holder.